2020
DOI: 10.1016/j.msec.2019.110187
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of biomolecules on stent materials through mussel adhesive protein coating to form biofunctional films

Abstract: It is widely accepted that surface biofunctional modification may be an effective approach to improve biocompatibility and confer new bioactive properties on biomaterials. In this work, mussel adhesive protein (MAP) was applied as a coating on 316L stainless steel substrates (316L SS) and stents, and then either immobilized VEGF or CD34 antibody were added to create biofunctional films. The properties of the MAP coating were characterized by scanning electron microscope (SEM), atomic force microscope (AFM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Wang et al. recently reported the increased retention of VEGF on mussel-adhesion protein (MAP)-coated stents via carbodiimide chemistry [ 74 ]. However, covalent linking may cause protein denaturation and impairment of overall bioactivity.…”
Section: The Potential Delivery Methods Of Gdf11 In Chronic Wound Modelmentioning
confidence: 99%
“…Wang et al. recently reported the increased retention of VEGF on mussel-adhesion protein (MAP)-coated stents via carbodiimide chemistry [ 74 ]. However, covalent linking may cause protein denaturation and impairment of overall bioactivity.…”
Section: The Potential Delivery Methods Of Gdf11 In Chronic Wound Modelmentioning
confidence: 99%
“…For all regenerative purposes and translational intents, current and future endeavors utilizing cell-capture mechanism may continue in three directions: 1) combining cell-capture molecules with other prohealing/proregenerative molecules; ( Chen et al, 2015 ; Zhang et al, 2015 ; Wang et al, 2020a ; Yang et al, 2020a ) 2) using more selective or specific molecules to recognize a subset of EPCs; ( Hirase, 2016 ; Tang et al, 2016 ) 3) exploiting EPC-derived secretomes such as those in the form of exosomes ( Zeng et al, 2021 ).…”
Section: Novel Developments and Challenges In Stentsmentioning
confidence: 99%
“…47 Building upon this approach, Wang et al recently demonstrated enhanced retention of VEGF on mussel-adhesion protein (MAP)-coated stents through carbodiimide chemistry. 48 MAP, which is rich in 3,4-dihydroxy-L-phenylalanine (Dopa), has immense celladhesive capacity. 49 MAP substrates coated onto a silicon wafer were dip-coated in VEGF, which was immobilized using EDC/ NHS chemistry.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…The tethered VEGF maintained its bioactivity, resulting in increased spreading of endothelial cells, while crosslinking of the MAP increased its retention on the stent. 48 Although covalent conjugation of proteins to materials prolongs local protein presentation within an implantation site, this strategy may reduce overall protein bioactivity by causing protein denaturation during processing or interfering with the ability of proteins to interact with cell integrins and receptors. [50][51][52][53][54][55] For example, modification of collagen I with EDC reduced cell adhesion by inhibiting cationic cell interactions with collagen's integrin binding domains.…”
Section: Biomaterials Sciencementioning
confidence: 99%
See 1 more Smart Citation